Unpacking the effects of conflict on fertilizer use and maize yields: Empirical evidence From Nigeria - Amare, Mulubrhan; Andam, Kwaw S.; Balana, Bedru; Olanrewaju, Opeyemi; Omamo, Steven Were (Wiley, 2026)
Conventional recommendations emphasize increasing the use of inorganic fertilizer to enhance maize yields in African countries south of the Sahara, but it is not clear how smallholders’ exposure to violent conflicts affect demand, yield responses, and the profitability of fertilizers. Our study tackles this question. We analyze how maize yield responds to fertilizer use and assess the profitability of fertilizer use in conflict-affected settings. We then investigate how conflict impacts the profitability of fertilizer, given that armed conflicts are likely to increase input costs, logistical difficulties, and market uncertainties. Our study reveals that yield responses to nitrogen are very low in Nigeria. We also show that exposure to conflict reduces input use rates and decreases the marginal physical productivity of nitrogen in maize production, making investment in fertilizer less profitable. Recognizing this effect of conflict on input use and maize yield response is crucial for targeting and resource allocation decisions among smallholders in similar conflict-affected regions. Moreover, the effect of conflict highlights how external factors, beyond the scope of agronomic practices, influence the economic incentives for fertilizer application and the resulting yield outcomes.